Seven deadliest USB attacks - Anderson, Brian (Brian James) (Syngress seven deadliest attacks series., 2010)
Do you need to keep up with the latest hacks, attacks, and exploits effecting USB technology? Then you need Seven Deadliest USB Attacks. This book pinpoints the most dangerous hacks and exploits specific to USB, laying out the anatomy of these attacks including how to make your system more secure. You will discover the best ways to defend against these vicious hacks with step-by-step instruction and learn techniques to make your computer and network impenetrable. Attacks detailed in this book include: USB Hacksaw USB Switchblade USB Based Virus/Malicous Code Launch USB Device Overflow RAMdump Pod Slurping Social Engineering and USB Technology Knowledge is power, find out about the most dominant attacks currently waging war on computers and networks globally Discover the best ways to defend against these vicious attacks; step-by-step instruction shows you how Institute countermeasures, don't be caught defenseless again, learn techniques to make your computer and network impenetrable.